The Relationship Between Students’ Physical Activity and Academic Stress (Baltic Journal of Sport and Health Sciences, 2021)
Background. Stress and physical inactivity are one of the most common risk factors among students. Problems of stress, experienced by students, and physical activity and impact on health are extremely important in order to improve students’ quality of life and prevent health problems.Methods. Academic stress was measured using the Konduri academic life stress questionnaire. Physical activity was evaluated by the Godin leisure time physical activity questionnaire. Distress was evaluated by the Reeder stress inventory. Study participants were 448 Lithuanian full-time first and third year bachelor’s students, with ages ranging from 18 to 39 years; average age 20.06 ± 18.04. 38 percent (173) of people under investigation were women, and 62 percent (275) were men. 60 percent (268) of people under investigation were first-year students, 40 percent (180) were third-year students.Results. Physically more active students experience less academic stress than less physically active students. Intense physical activity has the greatest impact on academic stress. Students who engage in intensive physical activity more often, experience less academic stress related to social support, motivation to achieve, training program and training mode, and self-confidence, compared with students who engage in intensive physical activity less often. It was found that women experience more academic stress, related to training program, academic aspirations, and career, compared with men. First-year students experience more academic stress, related to support, motivation to achieve, academic aspirations, self-confidence, and exam anxiety, compared with third-year students.Conclusions. Half of all students go in for sports three or more times a week, a third of students go in for sports less than three times a week, almost one-fifth of students never go in for sports. Increased physical activity is among men, first-year students, compared with women and third-year students. A fifth of students experience stress, almost half of students experience nervous tension; one-third of students do not experience tension and stress. Higher stress, both general and related to academic activities, is felt by women and first-year students, compared with men and third-year students.Keywords: students, physical activity, academic stress, stress.